Achieving a Representative Sample of Asian Americans in Biomedical Research Through Community-Based Approaches: Comparing Demographic Data in the All of Us Research Program With the American Community Survey. (January 2023) - Randal, Fornessa T.; Lozano, Paula; Qi, Siya; Maene, Chieko; Shah, Sameep; Mo, Yicklun; Ratsimbazafy, Francis; Boerwinkle, Eric; Cicek, Mine; Clark, Cheryl R.; Cohn, Elizabeth; Gebo, Kelly; et al.
Background: Underrepresented persons are often not included in biomedical research. It is unknown if the general Asian American population is being represented in All of Us . The purpose of this study was to compare the Asian demographic data in the All of Us cohort with the Asian nationally representative data from the American Community Survey. Method: Demographic characteristics and health literacy of Asians in All of Us were examined. Findings were qualitatively compared with the Asian data in the 2019 American Community Survey 1-year estimate. Results: Compared with the national composition of Asians, less All of Us participants were born outside the United States (64% vs 79%), were younger, and had higher levels of education (76% vs 52%). Over 60% of All of Us participants reported high levels of health literacy. Conclusion: This study had implications for the development of strategies that ensure diverse populations are represented in biomedical research.